The Role of Textual vs. Compound Input Enhancement in Developing Grammar Ability - Gholam-Reza Abbasian (Issues in Language Teaching, 2014)
The present study investigated comparatively the impact of two types of input enhancement (i.e. textual vs. compound enhancement) on developing grammar ability in Iranian EFL setting. Sixty-five female secondary high school students were selected as a homogenous sample out of about a 100-member population based on Nelson language proficiency test. Then, their grammar ability was measured based on a researcher-made diagnostic test prior to the experiment. The sample was randomly divided into two equal groups; one group received text-enhancement-based instruction of grammar, while the other received compound-based enhancement. Finally, they received an achievement test of grammar as a posttest to measure their progress in light of two different types of input enhancement mechanisms. The pertinent statistical analyses of the results indicated that a) the effect of textual enhancement-based instruction of grammar is not significantly meaningful, while b) the compound enhancement-based instruction has significant effect on learning grammatical structures. Comparatively speaking, therefore, c) compound enhancement-based instruction of grammar is more significantly effective than that of textual in developing grammar ability. It can be safely concluded that grammar instruction and its resultant development are subject to intervention type, which, pedagogically, bears promising messages for both teachers and syllabus designers to incorporate parameters of input enhancement in both teaching and materials development, respectively.